Women’s Contribution to Economic Growth in BRICS and Partner Countries: A Dynamic Modeling Approach - Galang Samudra; Ida Budiarty (Jurnal Ekonomi Pembangunan, 2026)
This study investigates the women’s contribution in driving economic growth in BRICS countries using a dynamic panel approach. It examines fertility, women’s education, and female labor participation, along with key macroeconomic controls, based on panel data from 14 countries over 2008–2022. The Generalized Method of Moments (GMM) is employed to address endogeneity and capture dynamic effects. The findings indicate that fertility, female labor force participation, and women’s education significantly promote economic growth, underscoring the importance of demographic factors, employment, and human capital. The negative interaction between fertility and female labor participation reflects a trade-off between reproductive and productive roles. Additionally, growth remains positively associated with carbon emissions, indicating reliance on carbon-intensive development. These results highlight the need for gender-inclusive and sustainable growth strategies